Cash transfers' role in improving livelihood diversification strategies and well-being: short- and medium-term evidence from Zimbabwe. (June 2022) - Pace, Noemi; Sebastian, Ashwini; Daidone, Silvio; Dela O Campos, Ana Paula; Prifti, Ervin; Davis, Benjamin
Highlights: The paper studies the impacts of the Zimbabwe Harmonized Social Cash Transfer program on livelihood strategies and household wellbeing. In the medium term, cash transfers increase opportunity-led diversification for vulnerable and resource-poor households. Cash transfers induce a medium-term change in livelihood strategies in both female- and male-headed households. Opportunity-led diversification increases food and non-food consumption. Abstract: This paper contributes to the literature on the determinants of rural livelihood diversification and its impact on household welfare in the short and medium term using data from a government-run social protection program in Zimbabwe. First, this study investigates whether cash transfers originally intended to ensure minimum food security in the poorest households can also induce the diversification of their livelihood strategies. Second, since diversification may lead to engagement in both low-return and high-return activities, this paper examines whether diversification resulting from the cash transfer increases household welfare. In the short run, the program causes only a small reduction in engagement in survival-led diversification; in the medium run, the program leads to a large shift from survival-led diversification and specialization in on-farm activities towards opportunity-led diversification. Further heterogeneity analysis shows that the program induces a medium-term change in livelihood strategies in both female- and male-headed households. In both time frames, opportunity-led diversification increases food and non-food consumption.